Experimental Research on Chloride Erosion Resistance of Rubber Concrete - Ruonan Zhu; Jianyong Pang; Tingya Wang; Xin Huang (Advances in Civil Engineering)
Chloride corrosion test was carried out in 4% NaCl solution to study the chloride corrosion resistance of rubber concrete. Rubber concrete was prepared by using 20 mesh, 1∼3 mm, and 3∼6 mm rubber particles instead of sand by 5%, 10%, 15%, and 20% of the cementitious material mass. The P-wave velocity and compressive strength of rubber concrete were measured. The microstructure of rubber concrete corroded by chloride was analyzed by SEM. The micromorphology was compared with the macrofailure characteristics under uniaxial compression. The results show that the rubber concrete was still in the early stage of erosion. With the increase of immersion time at the age of 110 days, the P-wave velocity and compressive strength of concrete were generally on the rise. Furthermore, during the period of erosion, the mechanical properties of rubber concrete increased with the increase of rubber particle size and decreased with the increase of the content. Therefore, when the rubber particle size was 3∼6 mm and the content was 5%, the antierosion performance was the best. This study has a certain guiding significance for the chloride corrosion resistance of rubber concrete.